Structural equation modelling assessment of personal and social factors on hajj crowding among african pilgrims in Mina - B, Alsolami; M R, Embi; W I, Enegbuma (International Journal of Engineering and Technology, 2018)
African pilgrimage to the Mecca date back to the early years of Islam through the Sahara desert. The perception of this group of pilgrims as they embark on the sacred Mina prayer rituals directly translates to how they perceived crowding in Mina. Hajj rituals are carried out at Mina for a minimum of three days. The optimum provision and continuous improvements of the facilities for pilgrims determines how this group reacts to the crowded environment which invariably affects their psychology. This paper assesses the impacts of personal factors (control, expectation, mood and sociability) and social factors (interpersonal similarity, provision of information and activities) on crowding levels perception among pilgrim groups from African origins. A self-administered survey instrument was used in the collection of data from the African origin Hajj group totaling 156 in number. Data analysis was carried out utilizing SPSS on the descriptive data and AMOS for multivariate Structural Equation Modeling (SEM). The survey instruments internal consistency, sample adequacy Kaiser-Meyer-Olkin measure and exploratory factor analysis (EFA) found that the validity was within acceptable thresholds. The pilgrim groups from African origins measurement model revealed that sociability and interpersonal similarity had the highest correlation while level of perceived crowing and activities had the lowest correlation. Furthermore, for personal factors, sociability had the highest inverse impact and for social factors, interpersonal similarity. The authorities formulating policies to managing crowd levels and perception will invariably be affected by adapting these research findings to improve the Hajj experience. Subsequently, assessing several other factors, which effect Hajj pilgrims such as physical factors, provides an avenue for future research.Â